A novel concept of unidirectional bridgeless combined boost-buck converter for EV battery chargers - Monteiro, Vítor Duarte Fernandes (2015)
This paper presents a novel concept of unidirectional bridgeless combined boost-buck converter for electric vehicles (EVs) battery chargers. The proposed converter is composed by two power stages: an ac-dc front-end converter used to interface the power grid and the dc-link, and a dc-dc back-end converter used to interface the dc-link and the batteries. The ac-dc converter is a bridgeless boost-type converter and the dc-dc converter is an interleaved buck-type converter. The proposed converter operates with sinusoidal grid current and unitary power factor for all operating power levels. Along the paper is described in detail the proposed converter for EV battery chargers: the circuit topology, the different stages describing the principle of operation, the power control theory, and the current control strategy, for both converters. Along the paper are presented several simulation results for a maximum power of 3.5 kW.